Association between endothelial and platelet function markers and adiponectin in renal transplanted recipients on cyclosporine and tacrolimus immunosuppression based therapy. (June 2015) - Sahin, Garip; Akay, Olga Meltem; Uslu, Sema; Bal, Cengiz; Yalcin, Ahmet Ugur; Gulbas, Zafer
Abstract: Aim: Coagulation abnormalities, endothelial dysfunction and arteriosclerosis play a key role in cardiovascular disease state observed in transplanted patients. Plasma adiponectin levels are lower following kidney transplantation. However, there is still a debate about this topic in the literature. This study evaluated, adiponectin levels associated with markers of endothelial dysfunction and platelet function in renal transplant patients. Methods: Sixty‐six renal transplant patients were studied. Patients were grouped according to immunosuppression regimen. Group 1 ( n =  36) were treated with cyclosporine A based regimes and group 2 ( n =  30) were treated with tacrolimus based regimes. Plasma adiponectin, asymmetric dimethyl arginine (ADMA), sP‐selectin levels and platelet aggregation tests were studied and were compared with those in control group ( n =  15, group 3). Results: Adiponectin, sP‐selectin and ADMA levels were higher in group 1 and statistically significant differences were observed compared with those of group 2 and group 3, respectively ( P  < 0.001, P  < 0.05, P  < 0.05). Platelet aggregation values induced by agonists were lower in group 1 than group 2 and group 3, but the difference did not reach statistical significance ( P  > 0.05). Conclusion: Adiponectin levels are elevated in line with ADMA and sP‐selectin levels. Since CsA induces higher adiponectin levels, platelet activation and endothelial dysfunction. These changes may be responsible for the increased risk of post‐transplant cardiovascular events in renal transplant patients. Summary at a Glance: This paper provides useful information in the filed of renal transplantation and hopefully promote better graft survival.